Correlation between antioxidant activity and bonding strength on bleached enamel - Hellen Caroliny De Carvalho; Ricardo Danil Guiraldo; Regina Célia Poli-Frederico; Sandra Mara Maciel; Sandra Kiss Moura; Murilo Baena Lopes; Sandrine Bittencourt Berger (Taylor & Francis Group, 2016)
Objective: This study used the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) method to evaluate the percentage of antioxidant activity (%AA) of green tea (GT) and sodium ascorbate (SA) gel in three concentrations (10%, 20% and 30%), and the influence of these concentrations on the microshear bond strength (μ-SBT) values of bleached enamel, using 10% carbamide peroxide (CP). Materials and methods: Eighty intact third molars were selected to perform the μ-SBT test, and were randomly divided into eight experimental groups: G1: positive control - no treatment; G2: negative control - bleached with CP; G3: PC +10% GT; G4: PC +20% GT; G5: PC +30% GT; G6: PC +10% SA; G7: PC +20% SA and G8: PC +30% SA. After applying the treatments, adhesive procedures were performed using Single Bond 2 and Filtek Z350XT. After 24 h, the samples were tested in a universal testing machine until fracture. The %AA was assessed in triplicate by DDPH method using a UV-VIS spectrophotometer. Results: In the μ-SBT, ANOVA revealed no significant difference between the antioxidants evaluated (p = .625), but did reveal significant effects of the concentrations studied (p = .007). A negative correlation was observed between μ-SBT and solution concentrations. The values of %AA were from 90.58 to 96.75. Conclusions: The reverse results occurred in μ-SBT values, only when the antioxidants were used in a 10% concentration and, %AA did not influence μ-SBT.